Transparent Defaults and Consent for Participation in a Learning Health Care System: An Empirical Study. (October 2020) - Dranseika, Vilius; Piasecki, Jan
We report a preregistered study that was designed to answer three questions about using transparent defaults to increase participation in a hypothetical learning health care system. Do default options influence consent to participate in learning activities within a learning health care system? Does transparency about default options decrease the effect of the defaults? Do people reconsider their choice of participation once they are informed about the defaults applied? In our study, application of the defaults did not have influence on rates of consent, nor did transparency about defaults have an effect on the rates of consent. Participants were also not likely to change their choice after being informed that defaults were applied to their previous choice. In general, our study raises doubts that defaults (both covert and transparent) can be used as an effective means in significantly increasing participation in learning health care systems.